Mechanisms Underlying the Strong Inhibition of Muscle-Type Nicotinic Receptors by Tetracaine - Cobo, Raúl; Nikolaeva, Magdalena; Alberola-Die, Armando; Fernández-Ballester, Gregorio; González-Ros, José M.; Ivorra, Isabel; Morales, Andrés (Frontiers in Molecular Neuroscience, 2018)
Nicotinic acetylcholine (ACh) receptors (nAChRs) are included among the targets of a variety of local anesthetics, although the molecular mechanisms of blockade are still poorly understood. Some local anesthetics, such as lidocaine, act on nAChRs by different means through their ability to present as both charged and uncharged molecules. Thus, we explored the mechanisms of nAChR blockade by tetracaine, which at physiological pH is almost exclusively present as a positively charged local anesthetic. The nAChRs from Torpedo electroplaques were transplanted to Xenopus oocytes and the currents elicited by ACh (IAChs), either alone or co-applied with tetracaine, were recorded. Tetracaine reversibly blocked IACh, with an IC50 (i.e., the concentration required to inhibit half the maximum IACh) in the submicromolar range. Notably, at very low concentrations (0.1 μM), tetracaine reduced IACh in a voltage-dependent manner, the more negative potentials produced greater inhibition, indicating open-channel blockade. When the tetracaine concentration was increased to 0.7 μM or above, voltage-independent inhibition was also observed, indicating closed-channel blockade. The IACh inhibition by pre-application of just 0.7 μM tetracaine before superfusion of ACh also corroborated the notion of tetracaine blockade of resting nAChRs. Furthermore, tetracaine markedly increased nAChR desensitization, mainly at concentrations equal or higher than 0.5 μM. Interestingly, tetracaine did not modify desensitization when its binding within the channel pore was prevented by holding the membrane at positive potentials. Tetracaine-nAChR interactions were assessed by virtual docking assays, using nAChR models in the closed and open states. These assays revealed that tetracaine binds at different sites of the nAChR located at the extracellular and transmembrane domains, in both open and closed conformations. Extracellular binding sites seem to be associated with closed-channel blockade; whereas two sites within the pore, with different affinities for tetracaine, contribute to open-channel blockade and the enhancement of desensitization, respectively. These results demonstrate a concentration-dependent heterogeneity of tetracaine actions on nAChRs, and contribute to a better understanding of the complex modulation of muscle-type nAChRs by local anesthetics. Furthermore, the combination of functional and virtual assays to decipher nAChR-tetracaine interactions has allowed us to tentatively assign the main nAChR residues involved in these modulating actions.